Physical growth of children and adolescents in China over the past 35 years - Xin-Nan Zong; Hui Li
Objective To examine if economic development in China correlates with physical growth among Chinese children and adolescents. Methods The height, body weight and physical activity level of children and adolescents aged 18 years and under, as well as dietary data, were obtained from seven large surveys conducted in China between 1975 and 2010. Chinese economic development indicators were obtained from the World Bank. Trends in body weight, height, economic data and diet were examined. Tests were conducted to check for correlations between height at 17 years of age and three indicators of economic development: gross domestic product, urbanization and infant mortality rate. Regional differences in physical growth were assessed. Findings Between 1975 and 2010, the growth of children and adolescents improved in tandem with economic development. The largest increment in height was observed during the period of puberty. Regional inequalities in nutritional status were correlated with disparities in economic development among regions. Over the past two decades, undernutrition declined among children less than 5 years of age, but in 2010 underweight and stunting were still common in poor rural areas. A large increase in obesity was observed in both urban and rural areas, but especially in large cities and, more recently, in small and medium-sized cities and affluent rural areas. Conclusion The average weight of children and adolescents has been increasing progressively since the 1970s. Current strategies to combat both child undernutrition and obesity need to be improved, especially in poor rural areas.